Catamenial (menstrual) pneumothorax is a complication of extragenital endometriosis - O V Voskresensky; M M Damirov; E A Tarabrin; I E Galankina; F A Sharifullin (IP Berlin A.V., 2015)
In Sklifosovsky RIEM for 10 years 27 women were operated on with spontaneous pneumothorax. Thoracic endometriosis was in 4 females, pneumothorax evolved during menstruation, but without the macroscopic features and morphological verification of thoracic endometriosis - in one woman. Overall endometriosis related complications amount to 5 patients (18,5%). This article describes two clinical observation of patients with catamenial spontaneous pneumothorax caused by thoracic endometriosis. This article shows the complexity of the diagnosis and treatment of this pathologic condition. Use of simultaneus approach of gynecologist, thoraxic surgeons, and radiologist - a way to successful treatment of such complications.